2004
DOI: 10.1021/ma049136y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Controlled Structure Reorganization in a Nanoorganized Polypeptide Multilayer Thin Film

Abstract: Aspects of poly(l-lysine) (PLL) and poly(l-glutamic acid) (PLGA) multilayer thin film assembly, physical properties of the films, and changes in film structure on pH shift have been studied by far-UV circular dichroism spectroscopy (CD), ultraviolet spectroscopy (UVS), ellipsometry, quartz crystal microbalance (QCM), and atomic force microscopy (AFM). We show that CD can be used to assess the secondary structure content of a polypeptide multilayer film deposited on quartz substrates by electrostatic layer-by-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(127 citation statements)
references
References 48 publications
12
113
2
Order By: Relevance
“…All of the CD spectra have a roughly similar shape. This implies that the peptides in all six films had approximately the same backbone structure and that all contained a significant proportion of residues in the same conformation, ␤ sheet [25,31,33,40], consistent with interpretation of Fourier-transform infrared spectra of polypeptide multilayer films [22,31,32].…”
Section: Spectroscopysupporting
confidence: 77%
See 2 more Smart Citations
“…All of the CD spectra have a roughly similar shape. This implies that the peptides in all six films had approximately the same backbone structure and that all contained a significant proportion of residues in the same conformation, ␤ sheet [25,31,33,40], consistent with interpretation of Fourier-transform infrared spectra of polypeptide multilayer films [22,31,32].…”
Section: Spectroscopysupporting
confidence: 77%
“…In Ref. [40], the average peak height of a 10-layer PLL (84 kDa)/PLGA (84.6 kDa) film prepared at pH 7.4 was less than 3.5 nm after dehydration. The values compare favorably with the results of the present study (Table 2).…”
Section: Afmmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have demonstrated that control over peptide sequence represents a means of control over useful film properties. [42][43][44] Assembly behavior of given polypeptides in a multilayer film will depend on propensity to form secondary structure, pH, ionic strength, presence of cosolvents, and so on. The broad range of process control variables enables the engineering of physical, chemical, and biological properties of multilayer filmbased structures.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of QCM to monitor viscoelastic changes in a molecule has been exploited to study the kinetic profile of absorption and associated conformational change of lysozyme on various surfaces (Shen et al, 2001), the role of hydration on the mechanism of allosteric regulation by in situ measurements of the oxygen-linked kinetics of water binding to haemoglobin (Salvay et al, 2003a(Salvay et al, , 2003b) and the density of protein (Voros, 2004) and peptide (Zhi and Haynie, 2004) layers subject to partial denaturation. QCM was used in the study of the coiled-coil protein motif, which occurs in over 200 proteins and which is of particular interest for a range of applications requiring surface immobilization of the constituent peptides (Stevens et al, 2004).…”
Section: Protein Interactions Protein Adsorptionmentioning
confidence: 99%